Efficacy of tripterygium glycosides combined with ARB on diabetic nephropathy: a meta-analysis - Wu, Xue (Biosci Rep, 2020)
The purpose of this meta-analysis was to evaluate the beneficial and adverse effects of tripterygium glycosides (TGs) combined with angiotensin II receptor blocker (ARB) on diabetic nephropathy (DN). We searched for randomized controlled trials (RCTs) in PubMed, Embase, Cochrane Central Register of Controlled Trials, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Data, Chinese Biomedical Literature Database, China Science and Technology Journal Database up to June 2017. Weighted mean difference (WMD) and standardized mean difference (SMD) were used for continuous variables and all variables were expressed by 95% confidence interval (CI). Twenty-three studies with 1810 DN patients were included in this meta-analysis. TG combined with ARB statistically significantly improved 24-h urinary total protein (24-h UTP) (SMD = −1.46; 95% CI = −1.84 to −1.09; P<0.00001), urinary albumin excretion rate (UAER) (SMD = −6.9; 95% CI = −9.65 to −4.14, P<0.00001), serum creatinine (SCr) (WMD = −7.65.14; 95% CI = −12.99 to −2.31; P=0.005) and albumin (Alb) (WMD = 5.7; 95% CI = 4.44 to 6.96; P<0.00001) more than did ARB alone. TG combined with ARB statistically significantly affected the level of serum glutamic pyruvic transaminase (SGPT) (WMD = 1.08; 95% CI = 0.04 to 2.12, P=0.04) more than did ARB alone. Compared with ARB alone, TG combined with ARB showed no significant difference in improving blood urea nitrogen (BUN) and hemoglobin A1c (HbA1c). Minor side effects from the combined treatment were observed and mainly focused on the abnormal liver function. TG combined with ARB offers a novel concept in treating DN, more high-quality RCTs are needed for better understanding and applying the combined treatment in DN.